Methanol oxidation process on the silver block catalysts; Reaction kinetics and catalysis letters; Vol. 52, № 2 - Pestryakov A. N. Aleksey Nikolaevich (1994, 1994)
By means of physico-chemical and structural-mechanical characteristics optimization a new type of silver catalyst has been worked out, viz. a porous metal block with cellular structure (foam silver). Activity and selectivity of the foam silver catalyst have been investigated in selective methanol oxidation.